2007
DOI: 10.1038/sj.emboj.7601775
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans septin complex is nonpolar

Abstract: Septins are conserved GTPases that form heteromultimeric complexes and assemble into filaments that play a critical role in cell division and polarity. Results from budding and fission yeast indicate that septin complexes form around a tetrameric core. However, the molecular structure of the core and its influence on the polarity of septin complexes and filaments is poorly defined. The septin complex of the nematode Caenorhabditis elegans is formed entirely by the core septins UNC-59 and UNC-61. We show that U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
126
0
24

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(155 citation statements)
references
References 53 publications
5
126
0
24
Order By: Relevance
“…It has been demonstrated that most septins present a C-terminal domain predicted to form a dimeric coiled coil whose function remains elusive (11)(12)(13)(14). The hallmark of a coiled coil is a repeating amino acid heptad pattern (a, b, c, d, e, f, and g) in which residues in positions a and d tend to be hydrophobic while those in positions e and g tend to be polar or charged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that most septins present a C-terminal domain predicted to form a dimeric coiled coil whose function remains elusive (11)(12)(13)(14). The hallmark of a coiled coil is a repeating amino acid heptad pattern (a, b, c, d, e, f, and g) in which residues in positions a and d tend to be hydrophobic while those in positions e and g tend to be polar or charged.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the importance of C-terminal interactions between septins of the SEPT6 and SEPT7 groups in diverse organisms (11,13,18), suggesting that they might form a coiled coil that would lend stability and/or play a role in determining preferential interaction between different septins in physiologically relevant filaments.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins of this family are ubiquitous in fungal and animal cells and typically localize to the cell cortex, where they appear to serve as scaffolds and diffusion barriers for other proteins that participate in a wide variety of cellular processes (Longtine et al 1996;Gladfelter et al 2001;Hall et al 2008;Caudron and Barral 2009). Despite the recent progress in elucidating the mechanisms of septin assembly ( John et al 2007;Sirajuddin et al 2007;Bertin et al 2008;McMurray and Thorner 2008), the details of septin function remain obscure. However, one prominent role of the septins and associated proteins is in cytokinesis.…”
mentioning
confidence: 99%
“…Structural analyses of worm and mammalian septins have revealed that the heteromeric, rod-shaped complex is conserved (19)(20)(21). Thus, septin rods characterized to date contain two copies of each septin subunit assembled into a nonpolar, heteromeric complex (Fig.…”
mentioning
confidence: 99%